First person - Stanley 'Michii' Kanai (The Company of Biologists, 2022)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Stanley 'Michii' Kanai is first author on ' Auriculocondylar syndrome 2 results from the dominant-negative action of PLCB4 variants', published in DMM. He is a postdoctoral fellow in the lab of Dr David Clouthier at Department of Craniofacial Biology, University of Colorado Anschutz Medical Campus, Aurora, CO, USA, investigating cell-signalling mechanisms in craniofacial development and disorders.